Pola Komunikasi Karyawan Tunarungu dalam Hubungan Kerja di PT Pou Yuen Indonesia - Sadikin, Firman; Rahayu, Hlida Sri (Universitas Majalengka, 2024)
This study aims to obtain an overview of the communication process of deaf disabled workers in working relationships at PT Pou Yuen Indonesia. This research uses a qualitative method with a case study approach. Data collection techniques were carried out using interview techniques, observation, Forum Group Discussion (FGD), and documentation. The results showed that the communication process of deaf employees in working relationships occurs primary using non-verbal language such as hand gestures, lip movements, written media, paper and cellphones. This primary process occurs when superiors, coworkers, and deaf employees ask questions, explain instructions or information related to work. In the secondary communication process, there is a special Whatsapp chat group for deaf employees which is used as a medium of information and communication between deaf employees and superiors and coworkers. Then the communication process can also be categorized as circular because there is a reciprocal process between deaf and non-disabled employees interactively during working hours every day.